MEASURING THE RELATIONSHIP BETWEEN GENERALISED ANXIETY DISORDER AND JOB PERFORMANCE - Habib , Mehnaz; Laidey , Nooraneda Mutalip (Electronic Journal of Business and Management, 2021)
This research investigates the prevalence of Generalised Anxiety Disorder (GAD) among female employees and its subsequent impact on job performance. Using the GAD-7 questionnaire as the primary instrument, a quantitative survey was conducted among 128 female employees from three institutions in Kuala Lumpur. The study found that 56% of female employees’ job performance is affected by GAD, leading to negative impacts on relationships with co-workers and supervisors. The findings suggest that early screening and intervention can help employees seek medical assistance while allowing employers to implement accommodation strategies—such as flexible scheduling and environmental modifications—to reduce absenteeism and sustain productivity.